MtDNA-maintenance defects: syndromes and genes - Viscomi, Carlo (J Inherit Metab Dis, 2017)
A large group of mitochondrial disorders, ranging from early-onset pediatric encephalopathic syndromes to late-onset myopathy with chronic progressive external ophthalmoplegia (CPEOs), are inherited as Mendelian disorders characterized by disturbed mitochondrial DNA (mtDNA) maintenance. These errors of nuclear-mitochondrial intergenomic signaling may lead to mtDNA depletion, accumulation of mtDNA multiple deletions, or both, in critical tissues. The genes involved encode proteins belonging to at least three pathways: mtDNA replication and maintenance, nucleotide supply and balance, and mitochondrial dynamics and quality control. In most cases, allelic mutations in these genes may lead to profoundly different phenotypes associated with either mtDNA depletion or multiple deletions.